Chemotherapy plus targeted drugs in conversion therapy for potentially resectable colorectal liver metastases: a meta-analysis - Wang, Lu (Oncotarget, 2016)
OBJECTIVES: To evaluate the safety and efficiency of the conversion therapy : chemotherapy plus anti-epidermal growth factor Receptor (EGFR) or anti-vascular endothelial growth factor receptor (VEGFR) monoclonal antibodies (MoAbs) with different rat sarcoma (RAS) status in patients with potentially resectable colorectal liver metastases (CRLM). METHODS: Randomized controlled trials (RCTs) were identified and the association between RAS mutation and clinical outcome in CRLM patients treated with anti-EGFR or anti-VEGFR MoAbs was investigated. Searches were performed for data recorded between January 2005 and August 2015 in the Cochrane Library, MEDLINE, PubMed, and EMBASE. Objective response rates (ORR), conversion resection rates (CRR), R(0) resection rates (R(0)R) and rate ratios (RR) were used to assess the strength of the association between different RAS status, MoAbs and conversion efficiency. RESULTS: In the conversion therapy, ORR and RR were associated with patients with wild type RAS and different MoAbs. Patients treated with MoAbs: anti-VEGFR or anti-EGFR drugs, resulted in higher ORR, (RR=1.53, 95% confidence interval [CI]: 1.27-1.84, P < 0.05). Furthermore, anti-EGFR regimens displayed higher ORR compared with anti-VEGFR regimens in CRLM patients, (RR=1.15, 95%CI: 1.04-1.26, P < 0.05). However, CRLM patients with mutant type RAS did not benefit from anti-EGFR therapy, (RR=0.91, 95%CI: 0.76-1.08, P<0.05) and wild type RAS patients displayed higher ORR with anti-EGFR therapy, (RR=1.56, 95%CI: 1.16-2.01, P <0.05). In addition, the patients achieved higher resection rates (RR=1.67, 95%CI: 1.00-2.81, P ≤ 0.05) and R(0) resection (RR=1.85, 95%CI: 1.04-3.27, P < 0.05). CONCLUSION: We noted that the addition of MoAbs (anti-EGFR or anti-VEGFR) to standard chemotherapy could improve conversion efficiency for patients with potentially resectable CRLM patients, and anti-EGFR therapies maybe more effective than anti-VEGFR therapies. RAS status is a potential predictive marker of the clinical benefit resulting from treatment with anti-EGFR MoAbs therapy in CRLM patients and anti-EGFR MoAbs therapy could displayed greater efficiency only in patients with wild type RAS.